Growth and salinity tolerance of wheat genotypes at early vegetative stage (Progressive Agriculture, 2017)
Growth and salinity tolerance study of wheat genotypes were conducted at regional agricultural research station to evaluate the selected wheat genotypes against salinity and to classify the wheat genotypes in different salt tolerant group. The experiment was carried out with 12 wheat genotypes under semi-controlled environment (inside plastic greenhouse) and natural light in a randomized complete block (RCBD).The materials were evaluated under control (non-saline) and 16 dS/m salinity level. A significant variation among the genotypes was observed for shoot length under both environments. The lowest reduction (2%) was found from G11 followed by G40 (4%). The genotypes showed differences in production of total shoot dry matter (TDM) at both non-saline and saline conditions.  The relative TDM per plant (% TDM to control condition) appears that three genotypes (G24, G33and G40) produced 90% RTDM. Salt tolerant genotype was found to be less affected at high salinity and could be produced better TDM compared to other genotypes. Three genotypes G24, G33 and G40 exhibited tolerant category. The distribution pattern of the genotypes into various salinity tolerance groups indicates that the overall pattern of behaviors of the genotypes tested remain fairly constant under two methods (based on RTDM and visual scoring).Progressive Agriculture 28 (1): 12-17, 2017